2016
DOI: 10.1074/jbc.m115.710251
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Peptide Recognition of an Amiloride-sensitive FMRFamide Peptide-gated Sodium Channel

Abstract: FMRFamide (Phe-Met-Arg-Phe-NH 2 )-activated sodium channel (FaNaC) is an amiloride-sensitive sodium channel activated by endogenous tetrapeptide in invertebrates, and belongs to the epithelial sodium channel/degenerin (ENaC/DEG) superfamily. The ENaC/DEG superfamily differs markedly in its means of activation, such as spontaneously opening or gating by mechanical stimuli or tissue acidosis. Recently, it has been observed that a number of ENaC/DEG channels can be activated by small molecules or peptides, indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 54 publications
3
40
0
Order By: Relevance
“…Here, we demonstrated that GMQ, a previously described nonproton ligand of ASIC3, can activate all four FaNaC orthologues via a mechanism distinct from the native FMRFamide peptide (35), but similar to the one used by GMQ to activate ASIC3 (27). Our data not only indicate a closer evolutionary relationship between ASIC and FaNaC subfamilies, despite the low sequence homology (12-18%), but also a conservation of the "GMQ-activation mode" that was already present in the common ancestor of these two subfamilies.…”
mentioning
confidence: 63%
See 3 more Smart Citations
“…Here, we demonstrated that GMQ, a previously described nonproton ligand of ASIC3, can activate all four FaNaC orthologues via a mechanism distinct from the native FMRFamide peptide (35), but similar to the one used by GMQ to activate ASIC3 (27). Our data not only indicate a closer evolutionary relationship between ASIC and FaNaC subfamilies, despite the low sequence homology (12-18%), but also a conservation of the "GMQ-activation mode" that was already present in the common ancestor of these two subfamilies.…”
mentioning
confidence: 63%
“…For the mutation HaFaNaC ⌬Gln-445-Ala-493 (with an ϳ50-residue truncation at the specific insertion II of the knuckle domain) (Figs. 1B and 8C), its apparent affinity (ϳ80-fold decrease), and the maximal currents of FMRFamide decreased profoundly (35). In contrast, the EC 50 of GMQ and the maximal currents were not changed by a truncation of Gln-445-Ala-493 ( Fig.…”
Section: Nonproton Ligand Of Asic3 Activates Fanacsmentioning
confidence: 87%
See 2 more Smart Citations
“…For FMRFamide, there have been three different receptors deorphanized in invertebrates so far. One is an FMRFamide-gated amiloride-sensitive Na + channel (FaNaCh) that has been identified in molluscs [45][46][47]. The two other receptors belong to two different groups of neuropeptide GPCRs.…”
Section: Introductionmentioning
confidence: 99%